2013
DOI: 10.3109/03014460.2013.857721
|View full text |Cite
|
Sign up to set email alerts
|

The role of physical activity, body mass index and maturity status in body-related perceptions and self-esteem of adolescents

Abstract: In summary, body mass index and physical activity plays an important role in body-related perceptions and self-esteem of adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 52 publications
(94 reference statements)
4
26
1
5
Order By: Relevance
“…These results are inconsistent with other researches which showed significant linear relationship/effect of PA on body image and BMI (2,13,17,30). However, our research results are consistent with the results of Rote et al He showed that lifestyle PA was unrelated to women's body image (4).…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…These results are inconsistent with other researches which showed significant linear relationship/effect of PA on body image and BMI (2,13,17,30). However, our research results are consistent with the results of Rote et al He showed that lifestyle PA was unrelated to women's body image (4).…”
Section: Discussioncontrasting
confidence: 98%
“…Some other studies have shown relationships between body mass index (BMI), body image and PA. Altintas et al indicated that BMI was the only predictor of perceived body attractiveness and body image for females (2). Negative association has been shown between body image and BMI (15,16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from the USA vary with gender and race, being overweight and physically inactive were both associated with low self-esteem in Hispanic adolescent girls [23]. In Turkey, both BMI and physical activity were positively associated with perceived body attractiveness in adolescent boys, while in girls, only BMI was positively associated with perceived body attractiveness [1]. Therefore, it is not clear if our observations are specific to Hong Kong adolescents, owing to the special culture in Hong Kong, where the West meets the East.…”
Section: Discussionmentioning
confidence: 94%
“…Altintas et al, in 2013 found that body mass index and physical activity play the most important role in body related perception and self-esteem of adolescents. 11 This suggests that besides a need for counseling and preparing adolescents for these changes and transitions, it is equally important to encourage physical activity and maintenance of normal weight.…”
Section: Discussionmentioning
confidence: 99%